2015
DOI: 10.1007/s11136-015-1077-5
|View full text |Cite|
|
Sign up to set email alerts
|

Burden of caregivers of adult patients with schizophrenia in a predominantly African ancestry population

Abstract: Poorer functioning and demographic factors were important determinants of caregiver burden. Community mental health services should include self-care interventions in rehabilitation programs in Jamaica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
4
25
0
7
Order By: Relevance
“…In a similar study conducted by Koukia and Madianos, no statistically significant difference was observed between caregivers’ gender and feelings of burden . When the literature was examined, it was found that caregivers of people with a diagnosis of schizophrenia were mostly women, and female caregivers had a higher care burden . In the studies conducted by Arslantaş et al.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In a similar study conducted by Koukia and Madianos, no statistically significant difference was observed between caregivers’ gender and feelings of burden . When the literature was examined, it was found that caregivers of people with a diagnosis of schizophrenia were mostly women, and female caregivers had a higher care burden . In the studies conducted by Arslantaş et al.…”
Section: Discussionmentioning
confidence: 88%
“…27,28 The literature has determined that the Zarit burden interview (ZBI) is widely used to determine the difficulties and burden experienced by caregivers. 2,11,[29][30][31] The ZBI involves 19 statements and can be applied to caregivers of patients with severe mental illnesses such as schizophrenia and Alzheimer's disease. [32][33][34] Psychiatric nurses, who spend the most time with patients and caregivers within the healthcare team, are the most active members of the team working on this issue.…”
Section: Whilementioning
confidence: 99%
See 2 more Smart Citations
“…Beban keluarga dalam merawat anggota keluarga skizofrenia merupakan suatu keadaan distres psikologis keluarga ditandai dengan meningkatnya kerja fisik, adanya tekanan emosional dan sosial akibat merawat anggota keluarga skizofrenia (Alexander et al, 2015). Keluarga dapat memiliki beban tinggi apabila keluarga tersebut tidak memiliki mekanisme koping yang adaptif (Chadda et al, 2007).…”
Section: Pembahasan Beban Keluarga Dalam Merawat Anggota Keluarga Skiunclassified